The Design of Arduino Uno Based Automatic Concrete Maker - Rangga Pradana Putra; Yusli Yenni (JEEMECS (Journal of Electrical Engineering, Mechatronic and Computer Science), 2020)
Making concrete manually is very time-consuming and energy-intensive. And if ordering concrete to the company can increase construction costs. The purpose of this research is to make concrete automatically with materials that are in accordance with Indonesian concrete standards so there is no need to order it again to the company. The tools used in this design are arduino uno , motor shield, sensors loadcell, servo motor, dc motor, solenoid valve, power supply, and button. The start button is connected to the pin on the arduino, then arduino is connected to the motor shield after it is connected to the servo motor, dc motor, loadcell, and the solenoid valve then given current by connecting the power supply to the motor shield and motor servo. The performance of this tool starts from pressing the button that matches the size of the concrete to be produced the the button signal will send to Arduino and the motor shield after that from the motor shield the signal is sent to the sand and rock servo motor, then it will be weighed with a loadcell sensor and poured what has been weighed into the blender to mix evenly, then the signal sent to the cement DC motor and solenoid valve to remove the cement and water to be mixed into the blender. After the stirring process is complete, the signal will be sent to the blender servo motor which will pour the concrete that has been processed. The design of the tool runs as desired.DOI : https://doi.org/10.26905/jeemecs.v3i2.4405